1998
DOI: 10.1007/pl00006313
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Three Lipocalin-Like Proteins Present in the Milk of Trichosurus vulpecula (Phalangeridae, Marsupialia)

Abstract: Three proteins have been identified in the milk of the common brush tail possum. Trichosurus vulpecula that from sequence analysis are members of the lipocalin family. They include beta-lactoglobulin, which appears to have two forms; a homologue to the late-lactation protein found in tammar, Macropus eugenii; milk; and a novel protein termed trichosurin. Whereas beta-lactoglobulin and trichosurin are both expressed throughout lactation, the late-lactation protein is not detected in samples taken before days 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…in cow's milk), and WAP (e.g. in rat milk), but additional whey proteins have been identified in marsupials, such as early lactation protein, late lactation protein, and trichosurin (Nicholas et al, 1987;Piotte and Grigor, 1996;Demmer et al, 1998;Piotte et al, 1998).…”
Section: Evolution Of Milk Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…in cow's milk), and WAP (e.g. in rat milk), but additional whey proteins have been identified in marsupials, such as early lactation protein, late lactation protein, and trichosurin (Nicholas et al, 1987;Piotte and Grigor, 1996;Demmer et al, 1998;Piotte et al, 1998).…”
Section: Evolution Of Milk Secretionmentioning
confidence: 99%
“…A b-lactoglobulin pseudogene is also suspected in the human genome, but there may be confusion with the glycodelin gene (Kontopidis et al, 2004). Other lipocalins (trichosurin, late lactation protein) are expressed in marsupial milk (Demmer et al, 1998;Piotte et al, 1998); however, these are only distantly related to b-lactoglobulin and are apparently of more recent origin (Ganfornina et al, 2000).…”
Section: Evolution Of Milk Secretionmentioning
confidence: 99%
“…Gel electrophoresis studies of possum milk proteins, carried out on a limited number of samples, showed that early lactation protein, late lactation protein and transferrin are differentially expressed between phase 2 and 3 of lactation (Grigor et al 1991, Piotte & Grigor 1996, Piotte et al 1997a. The aim of this study was to determine the developmental expression pattern of eight major milk protein genes throughout lactation in the possum using RNA slot blotting techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In phase 3 of lactation, milk production is at a peak and growth of the pouch young is greatest. We have recently cloned cDNAs for eight different milk protein genes which are abundantly expressed in the possum mammary gland (Piotte & Grigor 1996, Piotte et al 1997a observations). Some of these genes are homologues of proteins found in the milk of eutherian mammals, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation